Asal-usul dan makna angka: Perjalanan konsep bilangan dari India, dunia islam hingga Eropa - Khotimah, Husnul (Maliki Interdisciplinary Journal, 2026)
This study explores the origins and meanings behind numbers through a literature-based approach that traces the development of numeral systems from early civilizations to the modern era. The main focus of this research includes the invention of the concept of zero by the Indians, the role of Islamic civilization in transmitting and advancing the Indian numeral system, and the process by which this system entered Europe and eventually became known as Arabic numerals. Beyond the historical perspective, this study examines the mathematical and symbolic meanings of numbers across various cultures, demonstrating that numbers function not only as tools for calculation but also as symbols reflecting cultural worldviews and belief systems. The findings indicate that the development of numbers is a long evolutionary process shaped by practical needs, cultural contexts, and intellectual progress. Understanding the history of numbers is relevant to contemporary numeracy, particularly in improving society’s ability to interpret numerical information critically. Therefore, integrating historical and cultural perspectives into mathematics education is recommended to strengthen conceptual understanding and enhance numeracy skills in the information age.